Residual Effects of Repeatable Composting on Growth, Yield, and Uptake of Phosphorus Brassica Rapa.L Pakcoy - Anis Sholihah; Agus Sugianto (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2022)
This study aimed to determine the potential residues of the rice crop from the second planting period, which were fed with a mixture of pistia compost and rice straw of various compositions with the Brassica rapa L. pakcoy. The study used a factorial randomized block design, the first factor was 7 levels divided into 5 compost mixtures and 2 comparison treatments (NPK fertilizer treatment and control) as follows; control, M1 : 100% pistia, M2 : 75% pistia + 25% rice straw, M3 : 50% pistia + 50% rice straw, M4 : 25% pistia + 75% rice straw, M5 : 100% rice straw and M6 : NPK ., and the second factor is the presence or absence of addition of compost in the second rice planting period divided into 2 levels; 1. (+) = addition of compost, 2.(-) = no addition of compost. The results showed that the residue of composting for the second planting period of rice had a positive effect on soil fertility, especially in the repeated addition of compost, which showed a very significant positive priming effect. The highest positive priming effect was shown by the medium of high-quality compost, namely the treatment of 100% pistia (M1+) seen in the growth parameters and yield of Brassica rapa L pakcoy. The increase in growth due to the addition of repeated compost was 5.10% to 14.24%, and an increase in yield was 5.41% to 11.11% in various treatments of mixed compost media. The treatment with repeated addition of compost gave a significant response to the P uptake of Brassica rapa L plants but the treatment without compost (-) showed 36.72% higher than the treatment with the addition of compost (+).